Are Individual and Environmental Characteristics Associated With Running Performance in Female Runners of Different Age Categories? - Thuany, Mabliny; Malchrowicz-Mośko, Ewa; Kłoskowski, Dariusz; Gomes, Thayse Natacha (Frontiers in Psychology, 2021)
The purpose of this study was to identify the individual and environmental predictors associated with performance in female runners of different ages. The sample comprised 440 female Brazilian runners, who answered an online questionnaire, that provided information regarding height, weight, age (categories: “young adult”, “adult”, “early middle-age”, and “older adults”), socioeconomic status, and training characteristics (frequency and volume per week, running pace, race event, and running club participation). Information about environmental variables was obtained from the official institutes, and comprised the human development index (HDI), athletics events, athletic tracks, and female homicide. A linear regression model, clustered by state and performed by age groups, was computed. The sample presented a mean running pace of 5:57 min/km, and a mean BMI of 23.51kg/m-2. An increase in running pace and volume/week were observed with increasing age. In “young adults”, any of the variables were significantly associated with the performance. In “adult” group, only individual characteristics were statistically significantly related with the performance. In “early middle-age”, besides BMI (= 5.72; 95%CI = 3.65 – 7.79) and training volume (=-0.67; 95%CI= -1.07 - -0.27), the HDI was associated with the performance (= -23.30; 95%CI = -44.11 - -2.49). In older adults, it was found an association between socioeconomic status (= -19.47; 95%CI = -32.29 - -6.65), practice time (=142.92; 95%CI=89.34-196.50), running event participation (CI, athletic events (= 33.44; 95%CI = 15.16 – 51.72), and female homicide (=-0.11; 95%CI = -0.17 - -0.05) with the performance, highlighting the influence of both individual and environmental characteristics. Information about the role of these constraints, and their relationships, in female runners’ performance, can be used to guide the development of projects/strategies aiming to increase their involvement in physical activities and sports practice, through the promotion of a more “friendly environment” to women, and providing support for decision-makers when suggesting/implementing public policies.